Investigation of Protein and Epitope Characteristics of Oats and Its Implications for Celiac Disease - Gell, Gyöngyvér; Bugyi, Zsuzsanna; Florides, Christakis George; Birinyi, Zsófia; Réder, Dalma; Szegő, Zsuzsanna; Mucsi, Edina; Schall, Eszter; Ács, Katalin; Langó, Bernadett; Purgel, Szandra; Simon, Katalin; et al. (Frontiers in Nutrition, 2021)
The use of pure oats (oats cultivated with special care to avoid gluten contamination from wheat, rye and barley) in the gluten-free diet (GFD) represent important nutritional benefits for the celiac consumer. However, emerging evidence suggests that some oat cultivars may contain wheat gliadin analog polypeptides. Consequently, it is necessary to screen oats in terms of protein and epitope composition to be able to select safe varieties for gluten-free applications. The overall aim of our study is to investigate the variability of oat protein composition directly related to health-related and techno-functional properties. Elements of an oat sample population representing 162 cultivated varieties from 20 countries and the protein composition of resulting samples have been characterized. Size distribution of the total protein extracts has been analyzed by SE-HPLC while the 70% ethanol extracted proteins were analyzed by RP-HPLC. Protein extracts separated into 3 main groups of fractions on SE-HPLC column: polymeric proteins, avenins (both containing 3 subgroups based on their size), and soluble proteins, representing respectively 68.79-86.60%, 8.86-27.72%, and 2.89-11.85% of the total protein content. The ratio of polymeric to monomeric proteins varied between 1.37 and 3.73. 76 RP-HPLC-separated peaks have been differentiated from the ethanol extractable proteins of the entire population. Their distribution among the cultivars varied significantly, 6-23 peaks per cultivar. The number of appearances of peaks also showed large variation: one peak has been found in 107 samples while 15 peaks have been identified which appeared in less than 5 cultivars. An estimation method for ranking the avenin-epitope content of the samples has been developed by using MS spectrometric data of collected RP-HPLC peaks and bioinformatics methods. Using ELISA methodology with the R5 antibody, a high number of the investigated samples were found to be contaminated with wheat, barley, or rye.